The Twilight of the Avant-Garde : Spanish Poetry 1980–2000 - Mayhew, Jonathan, 1960- (Book collections on Project MUSE., 2009)
Twilight of the Avant-Garde addresses the central problem of contemporary Spanish poetry: the attempt to preserve the scope and ambition of modernist poetry at the end of the twentieth century. Offering a critical analysis of Luis Garcìa Montero's "poetry of experience," and the work of Jose; Angel Valente and Antonio Gamoneda, among others, Mayhew challenges received notions about the value of poetic language in relation to the society and culture at large. Ultimately championing the survival of more challenging and ambitious modes of poetic writing in the postmodern age, this volume argues that the cultural ambition of modernist poetics remains alive and well in our age of cynicism